1992
DOI: 10.1111/j.1095-8649.1992.tb02610.x
|View full text |Cite
|
Sign up to set email alerts
|

Predation by Moses perch, Lutjanus russelli, and blue‐spotted trevally, Caranx bucculentus, on juvenile brown tiger prawn, Penaeus esculentus: effects of habitat structure and time of day

Abstract: The effects of habitat structure and time of day on predation success of Moses perch, Lufjanus russelli, and blue-spotted trevally, Caranx bucculentus, feeding on juvenile brown tiger prawn, Penaeus esculentus, were tested in the laboratory. Our experiments demonstrated that both softsubstratum, in which prawns can burrow, and seagrass habitats reduce predation rates by fish during daytime when compared to hard-substratum habitats. However, the protection offered by burrowing in a soft substratum during daytim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…Studies have shown that fish are probably the major cause of mortality to juvenile prawns (Minello et al 1989) but that the presence of vegetation often reduces the success of fish predators (Minello & Zirnrnerman 1983, Minello et al 1989, Laprise & Blaber 1992. This is consistent with the mortality rates of Penaeus esculentus and P aztecus because both these species live in vegetated habitats and have lower rates of natural mortality.…”
Section: Mortalitysupporting
confidence: 73%
“…Studies have shown that fish are probably the major cause of mortality to juvenile prawns (Minello et al 1989) but that the presence of vegetation often reduces the success of fish predators (Minello & Zirnrnerman 1983, Minello et al 1989, Laprise & Blaber 1992. This is consistent with the mortality rates of Penaeus esculentus and P aztecus because both these species live in vegetated habitats and have lower rates of natural mortality.…”
Section: Mortalitysupporting
confidence: 73%
“…Several studies have demonstrated the substrate influence on some shrimp biological processes, since shrimps live on the substrate or buried in it (Fuss Jr and Ogren 1966). The majority of species remains buried during the day and emerge at dusk, i.e., are most active in the period when they are least vulnerable to potential predators (Minello et al 1987, Laprise and Blader 1992, Sogard and Able 1994, Dall et al 1990, Negreiros-Fransozo et al 1999. Moctezuma and Blake (1981) noted that juveniles remain unburied for a longer period than adults do, because they need more food as a result of their high growth rate.…”
Section: Introductionmentioning
confidence: 99%
“…It is also commonly believed that reduced predation risk results in elevated densities of invertebrates and fish that inhabit soft bottom areas containing structurally complex submerged aquatic vegetation (SAV) (Gotceitas & Colgan 1987, Gotceitas 1990a, Laprise & Blaber 1992. Predation risk is generally thought to decrease with increasing habitat complexity, and many experimental studies have shown that increases in habitat structure decrease predation efficiency of fish and other epibenthic predators (Savino & Stein 1982, Minello & Zimmerman 1983, Johns & Mann 1987, Gotceitas 1990b.…”
Section: Introductionmentioning
confidence: 99%